The Role of Islamic Religious Education Teachers in Fostering Students' Morals at State Vocational High School 1 Banyudono - Ginting, Mohamad Zein Hamdan Athalah; Salim, Hakimuddin (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
Personality is a crucial factor for the success of students in the learning process. Instilling good habits from an early age is very important for students. Teachers play a significant role in schools, especially Islamic Education (PAI) teachers, who are educators directly responsible for moral development and the inculcation of legal norms concerning right and wrong, as well as responsibility. This study aims to determine the roles, methods, supporting factors, and obstacles faced by PAI teachers in shaping the personalities of students at SMKN 01 Banyudono Boyolali. The approach used is qualitative, employing case study research methods through data collection techniques such as observation, interviews, and documentation. The results of this study conclude that PAI teachers play an essential role in the moral development of students at SMKN 1 Banyudono, primarily as educators, guides, habituators, and implementers of religious activities. Efforts made by PAI teachers to cultivate students' morals include encouraging the habit of reciting "basmallah" at the beginning of learning activities, saying "hamdallah" at the end, starting lessons by reciting Asma’ul Husna, maintaining classroom cleanliness, assigning additional tasks to memorize prayer recitations, promoting Quranic literacy, guiding and setting an example for students to perform congregational prayers, and actively participating in the execution of religious activities.